2012
DOI: 10.26727/njrcm.2012.1.3.139-143
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Quality of Life of Elderly Population in Mettupalayam, a Rural Area of Tamilnadu

Abstract: There has been an increase in the number of old aged people in all the countries in both absolute and proportional terms. Share of the elderly population of the world was 13% around 2000 and in India as per 2001 census the population of elderly was 76.6 million 1 as compared to 20 million in 1951. Thus the elderly account for 7.5% of the total population, in which elderly male are 7.1% and elderly female are 7.8% 4. This increasing number of elderly has a great demand on the health services and social security… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 5 publications
(4 reference statements)
11
20
1
Order By: Relevance
“…The results of our study are consistent with the results of studies conducted in India (Hameed et al, ; Sowmiya & Nagarani, ) and Myanmar (Naing et al, ). In these countries, the majority of older adults living in rural areas face economic burden.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study are consistent with the results of studies conducted in India (Hameed et al, ; Sowmiya & Nagarani, ) and Myanmar (Naing et al, ). In these countries, the majority of older adults living in rural areas face economic burden.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, QOL is defined by the World Health Organization (WHO) as “an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns” (WHO, , p.3). Using this definition and the same measuring tool of QOL among older adults in developing countries, such as India, the overall QOL score was found to be at moderate levels (Hameed, Brahmbhatt, Patil, Prasanna, & Jayaram, ; Sowmiya & Nagarani, ). QOL was also found to be at moderate levels among older adults in Myanmar (Naing, Nanthamongkolchai, & Munsawaengsub, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Females shows higher value in both domain. In studies done by Akbar et al, Sowmiya et al, Raj et al and Quadri et al, gender was found to be associated with QOL but opposite findings were observed by Praveen et al and Barua et al 10,[14][15][16][17][18][19] In present study there was significant association between elderly living in joint family and QOL score. Studies done by Sowmiya et al, Kumar et al showed that the elderly living in joint families had better QOL than in nuclear families.…”
Section: Discussioncontrasting
confidence: 51%
“…Concordant findings were observed by Praveen et al but Sowmiya et al and Kumar et al did not find any association between age and QOL. [14][15][16] Gender was significantly associated with QOL in two facets namely DAD and intimacy. Females shows higher value in both domain.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to our findings, they showed elderly people in institutions had scored the least in the domain of social relationships in QoL [36]. Furthermore, studies done with community elderly who had scored the highest in social relationships [37] and physical health [38], with least in psychological health [38] and physical health domains [37] in QoL, were mentioned. Although in our study, the environment domain scored the highest and social relationships domain scored the least in QoL, a study in Brazil has insisted on contradictory results [17].…”
Section: Discussionsupporting
confidence: 90%